'Knocking at the door of humanity': using co-creation and community-based participatory research to foster citizenship for individuals with lived experience of dementia. Issue 2 (3rd April 2023) - Reid, Colleen; Landy, Ania; Henderson, Julia
ABSTRACT: The lived experience of dementia includes loss of identity due to the negative and pessimistic social narratives that are stigmatizing and socially isolating. In the community-based participatory research (CBPR) project Raising the Curtain on the Lived Experiences of Dementia, eleven individuals living with dementia participated as 'peer collaborators' in weekly co-creative workshops over two years. The purpose of this study was to investigate how peer collaborators described their involvement in Raising the Curtain in relation to their social participation and ability to effect social messages about dementia. Data gathered from the workshops, including transcripts (8) and one-on-one evaluation interviews (103), were used for analysis. Research findings revealed that the participants' engagement as peer collaborators fostered their ability to enact resistance and social citizenship, including sharing lived experiences, combating the stigma of dementia, engendering inclusion and belonging, and promoting advocacy. Using CBPR to foster social citizenship suggests that meaningful and purposeful approaches to leisure are possible for individuals living with dementia.